Hospital and emergency department use in the last year of life: a baseline for future modifications to end-of -life care - Rosenwax, Lorna; McNamara, Beverley; Murray, Kevin; McCabe, Rebecca; Aoun, Samar; Currow, David (Australasian Medical Publishing Company Pty. Ltd., 2011)
Objectives: To describe hospital and emergency department use in the last year of life by people for whom death from cancer or one of another nine conditions was an expected outcome. Design, participants and setting: Retrospective cross-sectional study based on death registrations and morbidity data for 1071 Western Australians who died between 1 August 2005 and 30 June 2006. Decedents had an informal primary carer, did not live in residential aged care and died of a condition amenable to palliative care. Main outcome measures: Total number of hospital admissions; emergency presentations (with and without hospital admission); days spent in hospital by age group at death, sex, metropolitan or rural place of residence and cancer versus non-cancer diagnosis; proportion in hospital on any day in the last 365 days of life; time points of change in the last 365 days of life at which there was an increasing proportion of hospital admissions for those with cancer and non-cancer conditions. Results: All but 4% of the decedents spent time in hospital with a marked increase in hospitalisations in the last 108 days of life for people who died of cancer and the last 83 days of life for people who died of non-cancer conditions. Those with cancer spent less time in hospital than those with other diagnoses. Seventy per cent of the cohort had at least one emergency presentation. On the last day of life, 61.5% of people were in hospital and 4.0% had been seen in emergency departments. Conclusions: Western Australian hospitals currently provide extensive and progressively greater care at the end of life. Identifying patterns of emergency and inpatient use for various disease trajectories will assist in the planning of appropriate services for people where death is an expected outcome.